Pemberdayaan Kader Posyandu Dalam deteksi Dini Kejadian Stunting di Desa Tondomulyo Kecamatan Jakenan Kabupaten Pati - Amelia Nur Hidayanti; Siti Muawamah (LPPM AN Nuur, 2022)
Background: Stunting is a form of chronic malnutrition and is manifested in the form of failure to thrive which can begin in the womb until the child is two years old. The three main factors that cause stunting are unbalanced nutritional intake, a history of infectious diseases, and low birth weight. The bad impact caused by nutritional problems is the disruption of brain development, intelligence, physical growth disorders and disorders of the body's metabolism. Purpose: To increase cadre awareness about stunting, increase cadre skills in early detection of stunting events using KMS and growth charts and educate the public in stunting prevention in Tondomulyo village. Method: A community empowerment approach that involves the community directly as the subject and object of implementing community service activities. Results: After being given training, previously given information about educational materials on how to detect stunting early, monitoring growth and development of toddlers, providing good nutrition for toddlers and how to plot in the KSM book. Cadres are able to do early detection of stunting and provide education about stunting prevention, especially feeding to toddlers and how to plot in the KMS book, detect and promote stunting prevention around their homes Conclusion: Success in cadre training activities requires strong support from various parties. In addition, the continuity of the program at the posyandu requires the cooperation and dedication of the managers, including posyandu cadres. If the management can be done well, it will support the formation of cadre skills in early detection of stunting events using KMS and growth charts.